BUDAYA LOKAL SEBAGAI MEDIA RESOLUSI DAN PENGENDALIAN KONFLIK DI PROVINSI MALUKU (KAJIAN,TANTANGAN DAN REVITALISASI BUDAYA PELA) - Samsul Ode (Politika: Jurnal Ilmu Politik, 2015)
Local culture is a priceless national asset. An effort of making the culture uniform by the New Order government in the past gives effect to the resilience and growth of the local culture in Indonesia. In fact, if we examine it carefully, the local culture contains norms and values that organize people’s lifes. One of them is as a resolution tool/media and conflict control. Pela is one of the local culture that is still a community tradition in Maluku. Pela is the kinship between civil community formed by bonding in terms of areal and descent. In the pela, it embodied norms, values, and resolution mechanisms and conflict control. This study intends to examine how values in the pela able to be the resolution tool/media and the conflict control in Maluku’s people. Also, this study examines the challenges faced in pela application and the efforts that have been made in order to revitalize the pela. In the research, this study uses exploratory method. The result shows that the pela plays an important role as a resolution mechanism and conflict control.